2001
DOI: 10.1007/s001010100200
|View full text |Cite
|
Sign up to set email alerts
|

Immunsystem und primäre Kopfschmerzsyndrome

Abstract: The association between pain and inflammation and certain clinical signs led physicians to suspect a connection between immunological mechanisms and headache syndromes even years ago.This review intends to give an overview of the literature which deals with immunological mechanisms in headache syndromes -with divergent results.Thus, a food allergy as a cause of migraine only seems to be relevant in a few isolated cases.Immunoglobulins or infections do not seem to play a role.Whether the complement system, auto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 53 publications
0
1
0
2
Order By: Relevance
“…Although the groups were homogeneous in terms of age, sex, and disease duration and course, the higher number of attacks in the control group compared to the MS group may have caused a higher prevalence of headache in the control group and thus no difference between the groups. It was suggested that the proinflammatory immune response may be responsible for the pathogenesis of headache (28,29). Patients with psoriasis were the majority of the patients in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Although the groups were homogeneous in terms of age, sex, and disease duration and course, the higher number of attacks in the control group compared to the MS group may have caused a higher prevalence of headache in the control group and thus no difference between the groups. It was suggested that the proinflammatory immune response may be responsible for the pathogenesis of headache (28,29). Patients with psoriasis were the majority of the patients in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Ein Beweis für diese Kausalitätskette steht aber noch aus. Gezeigt wurde allerdings, dass bei Patienten mit Migräne im Vergleich zu Gesunden vermehrt proinflammatorische Zytokine im Serum nachzuweisen sind [17]. Auch weiß man, dass es im Rahmen einer systemischen Entzündung (z.…”
Section: Migräne Und Gastrointestinale Beschwerdenunclassified
“…Neben diesen Befunden gibt es einige, z. T. aber nicht einheitliche Ergebnisse, die bei Patienten mit Migräne und Clusterkopfschmerz auch Auffälligkei-ten bei verschiedenen Zytokinen wie z. B. TNF-α und IL-2 beschreiben (Übersicht in [12]). Gerade TNF-α spielt aber auch eine wichtige Rolle in der Regulation des Schlafes [61], sodass auch hier eine Verbindung zwischen Schlafstörungen und Kopfschmerz gesehen werden kann.…”
Section: Pathophysiologieunclassified